Utilização de análise multicritério para implantação de um modelo de logistíca reversa de embalagens vazias de agrotóxicos para a Bacia Hidrográfica do Jaguaribe-CE - Silva, José Pedro Varela da (2018)
In Brazil, as in many other countries, agriculture acts as an important economic development. The ease of acquisition, as well as the indiscriminate use of agrochemicals to combat pests and increase agricultural productivity, has been generating a series of environmental concerns. This led to the concern and need to treatment of empty agrochemical packaging, due to the risks human health and the environment when discarded improperly. In this sense, Law 9,974 / 2000 was created, as well as the Decree Law 4,074 / 2002, which regulates reverse logistics of empty agrochemical packaging. This work aimed to analyze the logistics process of empty agrochemical packaging by means of semi-structured questionnaires for those directly involved in this sector, as well as to optimize a system of reverse logistics that would be efficient. The technique used was based on the Analytic method Hierarchy Process (AHP), whose main objective is to develop an allocation methodology of empty packaging containers in all municipalities Jaguaribe-CE Hydrographic Basin. This method (AHP) was chosen due to its functionality, flexibility and great application in engineering problems to make decision involving multiple criteria. The producers, the distributors / resellers agrochemicals and the Ubajara receiving station, were the sectors interviewed, and the results demonstrated that the reverse logistics process is inefficient in almost all all of them. This is because, the data indicate, the percentage of packages returned producers does not differ much from those destined for the dump, except for happens in the Salgado Basin. The Jaguaribe Basin presented the worst scenario, where 56% of the interviewees (Jaguaribe), 31.4% (Jaguaribara) and 61.7% (Solonópole), showed that the more usual disposal adopted by local producers is usually the dumping ground. In relation to only 38% reported receiving empty containers when returned by the producers. The receiving office, in turn, stated that 83% of the packaging received comes from the municipalities of the Serra de Ibiapaba. By application of the multicriteria analysis, the methodology suggested that the allocation of 37 sub- would be a viable alternative to improve the reverse logistics of empty packaging of pesticides in the Jaguaribe Basin.